Development and performance analysis of the 200 keV Cockcroft-Walton ion accelerator - H.R. Mirzaei; S.H. Sanaye; B. Yadollahzadeh; M. Shirshekan; M. Asl beigi; O. Hasanpour; Z. Riazi Mobaraki; F. Ghasemi; A. Mohammadi; M. Sadafi Biabli; A. Abbasi; M. Nazari; et al. (Results in Physics)
This study reports the successful design, construction, and testing of a 200 keV electrostatic ion accelerator at NSTRI, emphasizing its beam transport performance and diagnostic capabilities. The system features a 13.56 MHz inductive RF ion source, a 200 kV high-voltage power supply, an acceleration section, a multi-component beam transport and diagnostic setup. Experimental results demonstrate a maximum beam current of 600 µA. Optimized beam dynamics, confirmed through simulations and experiments, yield focused beam profiles with RMS sizes of 4.2 mm (x) and 3.8 mm (y) at 150 keV. The diagnostic system, equipped with quadrupole and dipole magnets, enables precise measurement of beam current, divergence, emittance, and momentum spectrum. These results validate the accelerator performance, its agreement with simulations and its potential for advancing low-energy ion beam applications.